The Effectiveness of Cognitive Behaviors Therapy Group Counseling with Cognitive Restructuring Techniques and Cinematherapy Techniques to Reduce Academic Anxiety - Fithri Ananda, Chair; Puji Sugiharto, Dwi Yuwono; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Academic anxiety is experienced by many students of SMP Negeri 14 Bengkulu City. This study aims to examine the effectiveness of group counseling on cognitive behaviors therapy with cognitive restructuring techniques and cinematherapy techniques to reduce academic anxiety. A total of 21 students were involved in experimental research using a randomized pretest-posttest comparison group design. Analysis of the results of the paired sampled t test and post hoc test showed that group counseling cognitive behaviors therapy with cognitive restructuring techniques and cinematherapy techniques and the combination of the two techniques were effective in reducing academic anxiety. The combination group counseling of the two techniques is more effective in reducing student academic anxiety compared to group counseling of cognitive behaviors therapy with cognitive restructuring techniques and group counseling of cognitive behaviors therapy with cinematherapy techniques. This study recommends the use of group counseling a combination of both techniques to reduce student academic anxiety.